Wiser: A semantic approach for expert finding in academia based on entity linking. (May 2019) - Cifariello, Paolo; Ferragina, Paolo; Ponza, Marco
Abstract: We presentWiser, a new semantic search engine for expert finding in academia. Our system is unsupervised and it jointly combines classical language modeling techniques, based on text evidences, with the Wikipedia Knowledge Graph, via entity linking. Wiser indexes each academic author through a novel profiling technique which models her expertise with a small, labeled and weighted graph drawn from Wikipedia. Nodes in this graph are the Wikipedia entities mentioned in the author's publications, whereas the weighted edges express the semantic relatedness among these entities computed via textual and graph-based relatedness functions. Every node is also labeled with a relevance score which models the pertinence of the corresponding entity to author's expertise, and is computed by means of a proper random-walk calculation over that graph; and with a latent vector representation which is learned via entity and other kinds of structural embeddings derived from Wikipedia. At query time, experts are retrieved by combining classic document-centric approaches, which exploit the occurrences of query terms in the author's documents, with a novel set of profile-centric scoring strategies, which compute the semantic relatedness between the author's expertise and the query topic via the above graph-based profiles. The effectiveness of our system is established over a large-scale experimental test on a standard dataset for this task. We show thatWiser achieves better performance than all the other competitors, thus proving the effectiveness of modeling author's profile via our "semantic" graph of entities. Finally, we comment on the use ofWiser for indexing and profiling the whole research community within the University of Pisa, and its application to technology transfer in our University. Highlights: Wiser, a new semantic search engine for expert finding in academia is proposed. A novel modeling for academic expertise through a small, labeled and weighted graph. A new set of scoring and ranking strategies for expert retrieval. Improvements of the state-of-the-art systems over a large-scale experimental test. Public available system deployed over the Research community of our University.